Intelligent evaluation model of basketball teaching reliability based on swarm intelligence and edge computing - Ding Hang Wang; Sile Jian (Journal of Cloud Computing: Advances, Systems and Applications, 2023)
Abstract Campus basketball culture is gradually affecting students’ sports spirit and sports accomplishment. As for the evaluation of basketball teaching achievements, the method of specified items is generally used for testing, which is highly subjective. It’s completely teacher-led, and teachers make relevant evaluations of students’ basketball behavior. Teachers can’t be absolutely fair and just in the evaluation, because teacher evaluation can be affected by many factors, such as teachers’ mood on that day, teachers’ affection for students, and so on, the traditional way of teacher basketball evaluation is easy to cause negative emotional impact on some students, so that students have negative emotions on basketball activities, and even affect their sports quality, and finally affect their health. Based on the evaluation method of basketball teaching, this paper introduced a reliability intelligent evaluation model based on swarm intelligence and edge computing and used this model to evaluate students’ performance in basketball teaching classes. Moreover, this paper designed a related experiment, the experimental results showed that boys and girls in basketball level gap was more obvious. As far as dribbling skills were concerned, the highest score of boy A was 91 points, while the lowest score of girl C was 54 points. The gap was quite large. At the same time, the introduction results of the reliability intelligent evaluation model were studied by using the questionnaire survey method. As can be seen from the results of the questionnaire, the number of people who are very interested in basketball teaching activities is obviously high, and the number of people who are still not interested in the six activities is no more than 2. Through the change data of students’ interests and attitudes, it was proved that the reliability intelligent evaluation model could improve the students’ enthusiasm for learning basketball courses, thus improving their sports quality. This study provided a reference value for the application of swarm intelligence and edge computing in the intelligent evaluation model of basketball teaching reliability, and provided a direction for the future development of basketball teaching.